A case study of the key factors and mechanism associated with mining site pollution control based on an E-platform management system. (March 2018) - Guo, Xuan; Zhang, XiaoXin; Yue, Jianwei; Zhu, Kun
Abstract: An E-platform framework method of mine site pollution control was proposed and tested with big-data of survey system, technology system, and expert decision system. The survey system was used to detect multiple factors and control indexes of the mining area. Key controlling factor and ecological risk index of pressure sensitive model was used to evaluate the pollution determining factors. The ecological footprint was applied to evaluate sustainable development capability. The technical system serves the entire organization and production. An alarming alert is activated when the combination pressure sensitive index is above the threshold value. The expert decision system provides legal basis and decision-making services. It can establish the relationship between metabolism and secondary market for recycling of resources. The resources will be re-allocated by turning on the physical, chemical, biological defensive methods correspondingly. Three sub-platform systems promote the virtuous cycle of multi-level market and the improvement of resource integration capability. The whole mining site was integrated at a new risk rank level for pollution control by big-data of E-platform framework. All progress and sub-systems links will be imported into the big-database of E-framework friendly. The real-time data can be shared by executable interface. The data structures, interfaces between subsystems, independence and systematic are well integrated. Highlights: E-platform framework method of mine site pollution control was proposed and tested initial. Algorithm model is constructed by multi-factors and control indexes analysis. Key factor and ecological risk index was used to evaluate pollution determining factors and ecological footprint was applied to evaluate sustainable development capability. Three levels control will be imported into large database with real-time interactive data update in cloud data.